Glass composition, pre-crystallized microcrystalline glass, single-crystal-phase curved microcrystalline glass, and preparation methods and applications of glass composition, pre-crystallized microcrystalline glass and single-crystal-phase curved microcrystalline glass
By regulating the composition of the glass composition and the content of each component, a single-crystalline curved microcrystalline glass was prepared, which solved the problems of low light transmittance and high haze in the existing curved microcrystalline glass, and achieved the effects of high light transmittance, low haze and high mechanical properties.
Patent Information
- Application Number
- CN202411953436.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing curved crystal glass has low light transmittance and high haze, making it difficult to meet application scenarios with high light transmittance requirements.
By reasonably regulating the composition of the glass composition and the content of each component, a single crystal surface microcrystalline glass is prepared, including only one crystal phase Li2Si2O5, which improves light transmittance and reduces haze.
It realizes the high light transmittance, low haze and high mechanical properties of single-crystalline surface microcrystalline glass, meeting the requirements for light transmittance and mechanical properties in application scenarios.
Smart Images

Figure CN119707296A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of glass technology, and in particular to a glass composition, pre-crystallized glass-ceramics and single-crystal phase curved glass-ceramics, and preparation methods and applications thereof. Background Art
[0002] Glass-ceramics, also known as microcrystalline jade or ceramic glass, includes a crystalline phase and a glass phase, and the ratio of the crystalline phase to the glass phase affects the performance of the glass-ceramics. In the actual production process, glass-ceramics containing one or more crystalline phases can be obtained by adjusting the composition of the oxides and the content of each component in the glass formula. Glass-ceramics not only has strong light transmittance, but also has excellent mechanical properties. At the same time, the microcrystalline phase in glass-ceramics can hinder the propagation path of microcracks and further improve the mechanical properties of glass-ceramics.
[0003] With the development of industry, curved glass is widely used in smart phones, tablet computers, smart hands and other fields. It can provide a better visual experience and grip, and also give electronic products a sense of technology and fashion. The existing curved microcrystalline glass processing process includes glass plate forming, glass plate nucleation and crystallization, crystallized glass plate thinning, crystallized glass plate cutting, CNC, polishing, 3D hot bending, chemical strengthening and other operations. The preparation process is complicated, and the prepared curved microcrystalline glass has low light transmittance and high haze. In actual application, it cannot meet the use requirements for application scenarios with high light transmittance requirements.
[0004] Because during the hot bending process, for example, there are many types of crystal phases in microcrystalline glass. When it is heated again during hot bending, its crystal phase type, crystal particle size, refractive index, Lab (chromaticity) value, haze, transmittance, etc. are difficult to control and are prone to yellowing or devitrification. At the same time, some types of crystal phases will undergo relatively large volume changes during the hot bending crystallization process, which can easily cause warping.
[0005] Therefore, how to improve the light transmittance of curved glass-ceramics and reduce its haze has become a problem that needs to be solved urgently. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a glass composition, a pre-crystallized microcrystalline glass and a single-crystal phase curved microcrystalline glass and a preparation method and application thereof. The present invention reasonably regulates the composition of the glass composition and the content of each component, and the single-crystal phase curved microcrystalline glass prepared includes only one crystal phase, has high light transmittance, low haze and high dimensional accuracy.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In the first aspect, the present invention provides a glass composition, which, calculated as oxides, comprises 2wt%-5wt% Al2O3, 2wt%-4wt% P2O5, 12wt%-15wt% Li2O, 2wt%-5wt% Na2O, 7wt%-10wt% ZrO2 and 0.1wt%-1.5wt% CaO, with the remainder being SiO2; the composition of the glass composition satisfies the following relationship, wherein ω represents the mass percentage: 0.3≤(ω(ZrO2)-ω(P2O5)) / (ω(Li2O)-ω(Na2O))≤0.75; 1.04≤(ω(ZrO2)-ω(Na2O)) / (ω(Al2O3)-ω(CaO))≤9.
[0009] Among them, A=(ω(ZrO2)-ω(P2O5)) / (ω(Li2O)-ω(Na2O)), B=(ω(ZrO2)-ω(Na2O)) / (ω(Al2O3)-ω(CaO)).
[0010] Specifically, 0.3≤(ω(ZrO2)-ω(P2O5)) / (ω(Li2O)-ω(Na2O))≤0.75, for example, it can be 0.3, 0.4, 0.5, 0.6, 0.7 or 0.75, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0011] Specifically, 1.04≤(ω(ZrO2)-ω(Na2O)) / (ω(Al2O3)-ω(CaO))≤9, for example, it can be 1.04, 2, 3, 4, 5, 6, 7, 8 or 9, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] In the present invention, SiO2 is a component constituting the glass skeleton and the main body of the glass network structure, which can improve the chemical stability, mechanical properties and processing properties of the microcrystalline glass. At the same time, SiO2 may also cause quartz or a solid solution of quartz to appear in the microcrystalline glass, so the amount of SiO2 needs to be within a specific range.
[0013] Preferably, the mass percentage of Al2O3 is 2wt%-5wt% in terms of the mass percentage of the oxide, for example, it can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] In the present invention, Al2O3 is a network intermediate oxide, which can form larger aluminum oxide tetrahedrons in microcrystalline glass, and can also produce larger gaps, which is beneficial to ion exchange, improves the effect of chemical strengthening, and can also improve the mechanical properties of microcrystalline glass. However, Al2O3 is an extremely refractory oxide, which will increase the viscosity of the glass, thereby increasing the difficulty of glass clarification and homogenization, and also increase the concentration of defects such as bubbles in the glass; further, Al2O3 can also significantly increase the glass microcrystallization temperature, inhibit the crystallization ability of the base glass, and also inhibit the formation of lithium disilicate Li2Si2O5, resulting in the formation of LiAlSi2O6 crystal phase, which reduces the glass transmittance. Therefore, the amount of Al2O3 needs to be within a specific range.
[0015] Preferably, the mass percentage of P2O5 is 2wt%-4wt% based on the mass percentage of the oxide, for example, it can be 2wt%, 2.5wt%, 3wt%, 3.5wt% or 6wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In the present invention, Li2O and P2O5 can react to form Li3PO4 crystal phase, and Li3PO4 crystal phase can further induce Li2O and SiO2 in the glass to react to form Li2SiO3, and finally form Li2Si2O5 crystal phase; on the other hand, P2O5 can also induce lithium metasilicate and quartz phase to precipitate, and it is impossible to form enough Li2Si2O5 crystal phase, which will also reduce the light transmittance of microcrystalline glass. Therefore, the amount of P2O5 needs to be within a specific range.
[0017] Preferably, the mass percentage of Li2O is 12wt%-15wt%, for example, 12wt%, 13wt%, 14wt%, 14.5wt% or 15wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, Li2O helps to form lithium disilicate crystal phase during the crystallization process. At the same time, Li2O will reduce the viscosity of the glass, further reduce the chemical stability and mechanical properties of the glass, and also lead to an increase in raw material costs. Therefore, the amount of Li2O needs to be within a specific range.
[0019] Preferably, the mass percentage of Na2O is 2wt%-5wt%, for example, 2wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In the present invention, Na2O can reduce the viscosity of the glass, making it easier to clarify and homogenize the glass during the preparation process. At the same time, more than 2% of Na2O will weaken the generation ability of petalite and facilitate the generation of lithium disilicate. Therefore, the amount of Na2O needs to be within a specific range.
[0021] Preferably, calculated as a percentage by mass of the oxide, the mass percentage of ZrO2 is 7wt%-10wt%, for example, it may be 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt% or 10wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In the present invention, ZrO2 can reduce the size of the crystal grains in the microcrystalline glass, which is conducive to further improving the transmittance of the glass. Furthermore, ZrO2 exists in both the glass phase and the crystal phase, which can improve the mechanical strength of the microcrystalline glass. In addition, ZrO2 can also cause the glass to be unable to crystallize uniformly. Therefore, the amount of ZrO2 needs to be within a specific range.
[0023] Preferably, the mass percentage of CaO is 0.1wt%-1.5wt%, for example, 0.1wt%, 0.5wt%, 1wt%, 1.3wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In the present invention, CaO increases the difference between the glass phase and the microcrystalline phase. Under high temperature conditions, CaO can reduce the size of the grains in the microcrystalline glass, thereby helping to improve the transmittance of the glass, and can also stabilize the crystal structure and improve the mechanical properties of the microcrystalline glass. Therefore, the amount of CaO needs to be within a specific range.
[0025] Preferably, calculated as oxides, the glass composition further comprises: any one of 0-1wt% K2O, 0-1wt% B2O3, 0-1wt% ZnO, 0-1wt% MgO or 0-1wt% Y2O3, or a combination of at least two thereof, typical but non-limiting combinations comprising a combination of K2O and B2O3, or a combination of ZnO, MgO and Y2O3.
[0026] Specifically, the mass percentage of K2O can be 0, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Specifically, the mass percentage of B2O3 can be 0, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Specifically, the mass percentage of ZnO can be 0, 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt% or 1 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Specifically, the mass percentage of MgO can be 0, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Specifically, the mass percentage of Y2O3 can be 0, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] The present invention reasonably regulates the composition of the glass composition and the content of each component, and uses the glass composition to prepare pre-crystallized microcrystalline glass, which can form nuclei at a relatively low temperature and ensure uniform crystal size. The ratio of the crystal phase to the glass phase of the obtained pre-crystallized microcrystalline glass is appropriate. On the other hand, during 3D hot bending, Na2O weakens the generation of the petalite crystal phase, reduces the size of the grains during the crystallization process, and the crystal phase is mainly Li2Si2O5; thereby further improving the transmittance of the glass, and improving the problems of increased haze, increased b value, and reduced transmittance caused by the growth of other crystals. At the same time, ZrO2, Na2O and CaO exist between the glass phase and the crystal phase, which improves the difference between the glass phase and the microcrystalline phase, and can also improve the bulk strength of the microcrystalline glass.
[0032] In a second aspect, the present invention provides a pre-crystallized glass-ceramics comprising the glass composition described in the first aspect, wherein the crystalline phase of the pre-crystallized glass-ceramics includes Li2Si2O5 and Li2SiO3.
[0033] Preferably, the ratio C of the crystal phase to the glass phase in the pre-crystallized glass-ceramics is 0.56-0.92, for example, it can be 0.56, 0.6, 0.7, 0.8, 0.9 or 0.92, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the crystal grain size D50 of the pre-crystallized glass-ceramics is ≤20 nm, for example, it can be 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the thickness of the pre-crystallized glass-ceramics is 0.3 mm-0.8 mm, for example, 0.3 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm or 0.8 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the average transmittance of the pre-crystallized microcrystalline glass in the wavelength range of 380nm-780nm is ≥90.1%, for example, it can be 90.1%, 90.5%, 91%, 91.5% or 92%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the b value of the pre-crystallized microcrystalline glass is ≤0.4, and the b value is the absolute value of the yellow-blue value when the glass thickness is 0.6 mm. For example, it can be 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.39 or 0.4, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the haze of the pre-crystallized glass-ceramics is ≤0.2%, for example, it can be 0.1%, 0.12%, 0.14%, 0.16%, 0.18% or 0.2%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In a third aspect, the present invention provides a single-crystal phase curved glass-ceramic prepared from the pre-crystallized glass-ceramic described in the second aspect, wherein the single crystal phase of the single-crystal phase curved glass-ceramic is a Li2Si2O5 crystal phase.
[0040] The single-crystal phase curved surface glass-ceramics prepared by the present invention can make the growth of grains easier to control during the crystal phase growth process, which can further improve the transmittance of the glass and improve the problems of increased haze, warping and poor dimensional accuracy caused by crystal growth. It can be understood that the crystal phase of the present invention is mainly Li2Si2O5, and a small amount of other crystal phases that are not intentionally generated are not excluded. The content of other crystal phases is small and will not affect the performance of the single-crystal phase curved surface glass-ceramics of the present invention.
[0041] Preferably, the crystal grain size D50 of the single-crystal phase curved glass-ceramics is ≤30 nm, for example, it can be 10 nm, 15 nm, 20 nm, 25 nm or 30 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the crystallinity of the single-crystal phase curved glass-ceramics is ≤70%, for example, it can be 60%, 62%, 64%, 66%, 68% or 70%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] Preferably, the average transmittance of the single-crystal phase curved glass-ceramics at a wavelength of 380nm-780nm is ≥91%, for example, it may be 91%, 91.2%, 91.4%, 91.6%, 91.8% or 92%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the single-crystal phase curved surface glass-ceramics has a warpage of ≤0.1 mm, for example, 0.02 nm, 0.04 nm, 0.06 nm, 0.08 nm or 0.1 nm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] Preferably, the b value of the single crystal phase curved microcrystalline glass is ≤0.3, and the b value is the absolute value of the yellow-blue value when the glass thickness is 0.6 mm, for example, it can be 0.2, 0.22, 0.24, 0.26, 0.28 or 0.3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the haze of the single-crystal phase curved glass-ceramics is ≤0.1%, for example, it may be 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.1%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the drop height of the single-crystal phase curved glass-ceramics is ≥1.5m, for example, it can be 1.5m, 1.6m, 1.7m, 1.8m, 1.9m or 2m, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Because the glass component Na2O will inhibit the formation of the petalite crystal phase, the crystal phase of the prepared pre-crystallized microcrystalline glass is mainly composed of two crystal phases: Li2Si2O5 and Li2SiO3. In the process of converting the pre-crystallized microcrystalline glass into a single crystal phase curved microcrystalline glass, the increase in temperature will cause Li2SiO3 to be converted into Li2Si2O5. Therefore, the single crystal phase curved microcrystalline glass prepared by the present invention is mainly composed of Li2Si2O5 crystal phase. At the same time, the single crystal phase can also ensure the performance of the curved microcrystalline glass, and realize the customized control of the performance of the curved microcrystalline glass. Furthermore, ZrO2 and CaO co-exist in the glass phase and the crystal phase, which can not only refine the size of the grains, but also improve the bulk strength of the microcrystalline glass.
[0049] In a fourth aspect, the present invention provides a method for preparing the single-crystal phase curved surface glass-ceramics as described in the third aspect, the preparation method comprising the following steps:
[0050] (1) After mixing the raw materials according to the formula, they are melted, clarified, homogenized and annealed in sequence to obtain plain glass.
[0051] (2) Pre-crystallizing the plain glass to obtain the pre-crystallized microcrystalline glass as described in the second aspect.
[0052] (3) The pre-crystallized glass-ceramics is subjected to 3D heat bending treatment to obtain the single crystal phase curved glass-ceramics.
[0053] Preferably, the melting temperature in step (1) is 1380°C-1450°C, for example, it can be 1385°C, 1395°C, 1400°C, 1410°C, 1420°C, 1440°C or 1450°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the thickness of the plain glass in step (1) is 0.6 mm-0.7 mm, for example, 0.6 mm, 0.61 mm, 0.63 mm, 0.65 mm, 0.67 mm, 0.69 mm or 0.7 mm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0055] Preferably, the pre-crystallization treatment in step (2) includes a nucleation treatment.
[0056] The present invention converts the plain plate glass into pre-crystallized microcrystalline glass having two crystal phases of Li2Si2O5 and Li2SiO3 through nucleation treatment. The pre-crystallized microcrystalline glass obtained by pre-crystallization treatment in the present invention has a small volume change and small warping during the hot bending crystallization process, which can further improve the dimensional accuracy of the curved microcrystalline glass.
[0057] Preferably, the temperature of the nucleation treatment is 540°C-640°C, for example, it can be 540°C, 560°C, 580°C, 600°C, 620°C or 640°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] Preferably, the time of the nucleation treatment is 2h-4h, for example, 2h, 2.5h, 3h, 3.5h, 3.8h or 4h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] The present invention performs pre-crystallization treatment on the plain plate glass through nucleation treatment, so that nucleation can be achieved at a lower temperature, the crystal size is uniform, the grain size is small, and the crystallinity is high.
[0060] Preferably, the 3D hot bending process in step (3) includes a preheating process, a hot pressing process and a cooling process performed sequentially.
[0061] During the 3D hot bending process, the Li2SiO3 crystal phase of the pre-crystallized glass is converted into Li2Si2O5 by increasing the temperature, thereby preparing a single-crystal phase curved surface microcrystalline glass containing only the Li2Si2O5 crystal phase. The single-crystal phase curved surface microcrystalline glass prepared by the present invention has high uniformity and light transmittance, low haze, and high mechanical strength of the body.
[0062] Preferably, the preheating treatment includes 3-5 preheating steps, for example, 3, 4 or 5 preheating steps.
[0063] Preferably, the hot pressing treatment includes 3-5 hot pressing steps, for example, 3, 4 or 5 hot pressing steps.
[0064] Preferably, the cooling treatment includes 3-5 cooling steps, for example, 3, 4 or 5 cooling steps.
[0065] Preferably, the working temperature of the preheat treatment is 460°C-760°C, for example, it can be 460°C, 480°C, 540°C, 610°C, 690°C, 700°C or 750°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] Preferably, the working time of the preheating treatment is 100s-500s, for example, it can be 100s, 200s, 300s, 400s or 500s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] Preferably, the working temperature of the hot pressing treatment is 720°C-800°C, for example, it can be 720°C, 730°C, 740°C, 750°C, 760°C, 760°C, 780°C or 800°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] Preferably, the pressure of the hot pressing treatment is 0.1 MPa-3 MPa, for example, it can be 0.1 MPa, 0.5 MPa, 1 MPa, 1.8 MPa, 2 MPa, 2.4 MPa or 3 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] Preferably, the working time of the hot pressing treatment is 50s-300s, for example, it can be 50s, 80s, 120s, 160s, 200s or 300s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] Preferably, the working temperature of the cooling treatment is 350°C-600°C, for example, it can be 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] Preferably, the working time of the cooling treatment is 100s-500s, for example, it can be 100s, 200s, 300s, 400s or 500s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] Preferably, after the 3D hot bending treatment, a chemical strengthening treatment is also performed.
[0073] Preferably, the chemical strengthening treatment comprises using a bath salt to perform ion exchange on the single-crystal phase curved glass-ceramics.
[0074] After chemical strengthening, single-crystal curved glass-ceramics can form a larger compressive stress and ion exchange depth, have good drop resistance, and its mechanical properties will be further improved.
[0075] Preferably, the bath salt comprises mixed molten salt.
[0076] Preferably, the mixed molten salt comprises NaNO3 and KNO3.
[0077] Preferably, the concentration of NaNO3 is 9wt%-40wt%, for example, 9wt%, 10wt%, 20wt%, 30wt% or 40wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] Preferably, the concentration of KNO3 is 59.8wt%-90wt%, for example, 59.8wt%, 60wt%, 70wt%, 80wt% or 90wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] Preferably, the mixed molten salt also includes LiNO3.
[0080] Preferably, the concentration of LiNO3 is 0.2wt%-1wt%, for example, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] Preferably, the temperature of the chemical strengthening is 460°C-500°C, for example, 460°C, 470°C, 480°C, 490°C or 500°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0082] Preferably, the chemical strengthening time is 3h-6h, for example, 3h, 3.5h, 4h, 5h, 5.5h or 6h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0083] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0084] (1) Preparing plain glass: preparing the plain glass by mixing the glass raw material components according to the glass composition described in the first aspect, and then melting, clarifying, homogenizing and annealing in sequence; the melting temperature is 1380°C-1450°C, and the thickness of the plain glass is 0.6mm-0.7mm.
[0085] (2) Preparing pre-crystallized glass-ceramics: Nucleating a plain glass plate at 540° C.-640° C. for 2 h-4 h, cooling the plate to room temperature, and preparing the pre-crystallized glass-ceramics.
[0086] (3) Preparation of single-crystalline curved glass-ceramics: The pre-crystallized glass-ceramics is subjected to heat bending treatment to obtain the single-crystalline curved glass-ceramics, wherein the heat bending treatment comprises 3-5 preheating steps, 3-5 hot pressing steps and 3-5 cooling steps performed in sequence, wherein the working temperature and working time of the preheating step are 460°C-760°C / 100s-500s, respectively; the working temperature, time and pressure of the hot pressing step are 780°C-800°C / 50s-300s / 0.1MPa-3MPa, respectively; and the working temperature and time of the cooling step are 350°C-600°C / 100s-500s, respectively.
[0087] (4) Preparation of chemically strengthened single-crystalline phase curved glass-ceramics: The single-crystalline phase curved glass-ceramics is kept at 400℃-420℃ for 30min-40min, and then immersed in a mixed molten salt for chemical strengthening for 3h-6h to obtain the chemically strengthened single-crystalline phase glass-ceramics; the holding temperature of the chemical strengthening is 460℃-500℃, the mixed molten salt includes NaNO3 with a concentration of 9wt%-40wt% and KNO3 with a concentration of 59.8wt%-90wt%, and the mixed molten salt also includes LiNO3 with a concentration of 0.2wt%-1wt%.
[0088] In a fifth aspect, the present invention provides an application of the single-crystal phase curved glass-ceramics as described in the third aspect, wherein the single-crystal phase curved glass-ceramics is applied to a touch display screen, a smart terminal or a photovoltaic power generation device.
[0089] Compared with the prior art, the present invention has at least the following beneficial effects:
[0090] (1) The present invention reasonably regulates the composition of the glass composition and the content of each component, so that the prepared microcrystalline glass includes only one crystalline phase, which is beneficial to improving the uniformity and light transmittance of the microcrystalline glass and reducing its haze.
[0091] (2) The present invention ensures that the content of each component satisfies a specific quantitative relationship, and then reasonably controls the relevant parameters of the pre-crystallized microcrystalline glass. After 3D hot bending treatment, the single-crystalline phase curved microcrystalline glass is prepared, which has a stable crystal phase structure and uniform grain size, which is beneficial to improving the mechanical properties of the microcrystalline glass.
[0092] (3) The present invention prepares single-crystal phase curved microcrystalline glass, which has high light transmittance, low b value, small haze, low warping and high dimensional accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0093] Figure 1 is a scanning electron microscope image of the single-crystalline curved glass-ceramics prepared by component 1 in Example 1 of the present invention;
[0094] Figure 2 This is the XRD diagram of the single-crystalline curved glass-ceramics prepared from components 1 to 3 and component 7 in Example 1 of the present invention. DETAILED DESCRIPTION
[0095] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0096] Example 1
[0097] This embodiment provides a glass composition, the chemical composition of the glass composition is as described in components 1 to 7 in Table 1, and the preparation method of preparing single-crystal phase curved surface micro-ceramics using the glass composition is as follows:
[0098] (1) after mixing raw materials according to the glass composition, sequentially melting, clarifying, homogenizing and annealing are performed to obtain plain glass; the melting temperature is 1380° C., and the thickness of the plain glass is 0.7 mm;
[0099] (2) nucleating the plain glass at 540° C. for 2 h and cooling to room temperature to prepare pre-crystallized glass-ceramics;
[0100] (3) subjecting the pre-crystallized glass-ceramics to a heat bending treatment to obtain the single-crystal phase curved glass-ceramics, wherein the heat bending treatment comprises five preheating processes, three hot pressing processes and three cooling processes performed in sequence, including firstly performing five preheating processes, wherein the working temperature and working time of the preheating processes are respectively 460°C / 50s, 520°C / 50s, 600°C / 50s, 660°C / 50s and 730°C / 50s, the working temperature, time and pressure of the hot pressing process are respectively 780°C / 50s / 0.1MPa, 800°C / 50s / 0.1MPa and 720°C / 50s / 0.2MPa, and the working temperature and time of the cooling process are respectively 600°C / 50s, 540°C / 50s and 450°C / 50s;
[0101] (4) The single-crystalline phase curved surface microcrystalline glass-ceramics is kept at 400°C for 30 minutes, and then chemically strengthened at 460°C for 6 hours to obtain chemically strengthened single-crystalline phase curved surface microcrystalline glass-ceramics; the chemical strengthening treatment includes using bath salt to perform ion exchange on the single-crystalline phase curved surface microcrystalline glass, and the mixed molten salt includes LiNO3 with a mass concentration of 0.2wt%, NaNO3 with a mass concentration of 40wt%, and KNO3 with a mass concentration of 59.8wt%.
[0102] The properties of the pre-crystallized glass-ceramics and single-crystal phase curved glass-ceramics prepared in this embodiment are shown in Table 1.
[0103] Figure 1 is a scanning electron microscope image of the single-crystalline curved glass-ceramics prepared by component 1 in Example 1 of the present invention, Figure 2 This is the XRD diagram of the single-crystalline phase curved glass-ceramics prepared by components 1 to 3 and component 7 in Example 1 of the present invention. It can be seen from the figure that the single-crystalline phase curved glass-ceramics prepared in this example has a uniform organizational structure and only includes one crystal phase of Li2Si2O5.
[0104] Example 2
[0105] Glass raw materials are weighed according to the proportion of 3D microcrystalline glass components of component 1 in Example 1 in Table 1, and plain glass is obtained according to the preparation method of step (1) in Example 1. Then, pre-crystallization treatment is carried out according to conditions 1 to 6 of Example 2 in Table 2 to obtain 6 groups of pre-crystallized microcrystalline glasses. The properties of the 6 groups of pre-crystallized microcrystalline glasses are shown in Table 2.
[0106] Example 3
[0107] Weigh glass raw materials according to the proportion of 3D microcrystalline glass components of component 1 in Example 1 in Table 1, and obtain plain glass according to the preparation method of step (1) in Example 1, then perform pre-crystallization treatment according to Condition 1 of Example 2 in Table 2 to obtain pre-crystallized microcrystalline glass, and then perform hot bending treatment on the pre-crystallized microcrystalline glass according to Condition 1-Condition 2 of Example 3 in Table 3 to obtain 2 groups of single crystal phase curved microcrystalline glasses. The properties of the 2 groups of single crystal phase curved microcrystalline glasses are shown in Table 3.
[0108] Example 4
[0109] Weigh glass raw materials according to the proportion of 3D microcrystalline glass components of component 1 in Example 1 in Table 1, and obtain plain glass according to the preparation method of step (1) in Example 1, then perform pre-crystallization treatment according to Condition 1 of Example 2 in Table 2 to obtain pre-crystallized microcrystalline glass, then perform heat bending treatment on the pre-crystallized microcrystalline glass according to Condition 1 of Example 3 in Table 3 to obtain single-crystal phase curved microcrystalline glass, then perform chemical strengthening treatment on the single-crystal phase curved microcrystalline glass according to Condition 1 to Condition 6 of Example 4 in Table 4 to obtain 6 groups of chemically strengthened single-crystal phase curved microcrystalline glasses, and the properties of the 6 groups of chemically strengthened single-crystal phase curved microcrystalline glasses are shown in Table 4.
[0110] Comparative Example 1
[0111] The difference between this comparative example and Example 1 is that, except that the raw materials in step (1) are configured according to the comparative component 1 in Table 1, the rest are the same as Example 1.
[0112] Comparative Example 2
[0113] Glass raw materials are weighed according to the proportion of 3D microcrystalline glass components in component 1 in Example 1 in Table 1, and plain glass is obtained according to the preparation method of step (1) in Example 1. Then, pre-crystallization treatment is carried out according to the conditions of Comparative Example 2 in Table 2 to obtain comparative pre-crystallized microcrystalline glass. The properties of the comparative pre-crystallized microcrystalline glass are shown in Table 2.
[0114] Comparative Example 3
[0115] Glass raw materials are weighed according to the proportion of 3D microcrystalline glass components of component 1 in Example 1 in Table 1, and plain glass is obtained according to the preparation method of step (1) in Example 1. Pre-crystallization treatment is then carried out according to the conditions of Comparative Example 2 in Table 2 to obtain pre-crystallized microcrystalline glass. The pre-crystallized microcrystalline glass is then hot-bent according to Conditions 1-2 of Comparative Example 3 in Table 3 to obtain 2 groups of curved microcrystalline glasses, and the properties of the curved microcrystalline glasses are shown in Table 3.
[0116] Test Method
[0117] Corresponding tests were performed on the chemically strengthened single-crystal phase curved surface glass-ceramics obtained in Examples 1 to 4 and Comparative Examples 1 to 3, and the test results were recorded in Tables 1 to 4, respectively. The tests included the following test methods:
[0118] Crystalline phase and crystallinity: The XRD diffraction peak is compared with the database spectrum to determine the crystal phase, and the crystallinity is obtained by calculating the proportion of the crystalline phase diffraction intensity in the overall spectrum intensity using the Rietveld method.
[0119] Average grain size: measured using a SEM scanning electron microscope. The glass-ceramics is surface treated in HF acid and then chrome-plated. The surface is scanned under a SEM scanning electron microscope to observe the diameter of the particles. The average diameter of all grain cross-sections is added up and divided by the number of grains in the SEM image.
[0120] b value: The color b value is tested using the Datacolor 650 ultra-high precision desktop spectrophotometer.
[0121] Transmittance: The transmittance of 0.6mm glass-ceramics at 560nm was measured using a Lambda950 UV-visible spectrophotometer from Perkin Elmer, USA, in accordance with GB / T40415 standard.
[0122] Haze: Use SUGA optical HZV3 haze meter to test the haze of samples according to GB / T2410 standard.
[0123] Warping: 3D bend a 0.6mm thick glass plate into 5.5 inches, and use a feeler gauge to measure the gap between the 3D bent glass plate and the measuring table (3D mold).
[0124] 180-grit sandpaper drop height: measured by a mobile phone controlled drop tester. The specific test conditions are: 180-grit sandpaper, 195g total weight, 30cm base height, 10cm increment, 1 time per height, until broken.
[0125] In the present invention, a Japanese Orihara FSM-6000LE+SLP1000 surface stress meter is used for testing, CS refers to the compressive stress value on the surface of the strengthened glass; CS-30 refers to the compressive stress value at a depth of 30 microns after the strengthened glass sample is strengthened by mixed salt; DOC refers to the ion exchange depth of the compressive stress layer of the strengthened glass.
[0126] Table 1
[0127]
[0128]
[0129] Table 2
[0130]
[0131]
[0132] Table 3
[0133]
[0134]
[0135] Table 4
[0136]
[0137] The test results show that:
[0138] (1) It can be seen from Examples 1 to 4 and Comparative Examples 1 to 3 that the single crystal phase of the single crystal curved glass-ceramics obtained by the present invention is Li2Si2O5 crystal phase by reasonably regulating the glass composition and the content of each component, and its average transmittance is ≥91%, warp ≤0.1mm, b value ≤0.3, haze ≤0.1%, and drop height ≥1.5m.
[0139] (2) It can be seen from Example 1 and Comparative Example 1 that the comparison components are not within the scope of the present application, wherein A is 0.17 and B is 0.36, which are not within the scope required by the present invention. The ratio C of the crystal phase to the glass phase of the obtained pre-crystallized microcrystalline glass is 1.22. The curved microcrystalline glass obtained by the subsequent 3D hot bending treatment has a haze of 0.3%, a b value of 0.6, and a warping of 0.2 mm, which does not meet the application scenarios of curved glass.
[0140] (3) It can be seen from Example 2 and Comparative Example 2 that by adjusting the process parameters of the nucleation treatment, the pre-crystallized microcrystalline glass-ceramics obtained in the present invention has a transmittance ≥90.1%, a b value ≤0.4, and a haze ≤0.2%. The nucleation treatment parameters used in Comparative Example 2 are not within the range required by the present invention, and the performance of the pre-crystallized microcrystalline glass-ceramics obtained is poor.
[0141] (4) It can be seen from Example 3 and Comparative Example 3 that the single-crystal phase curved surface microcrystalline glass-ceramics prepared by adjusting the process parameters of the hot bending treatment in the present invention has small grain size, low warping, high transmittance, and excellent comprehensive performance; the pre-crystallized microcrystalline glass-ceramics of Comparative Example 3 does not meet the requirements of the present invention, and the single-crystal phase curved surface microcrystalline glass-ceramics obtained by the hot bending treatment grows LiAlSi4O 10 Crystalline phase, the overall performance is poor, and it does not meet the application scenarios of curved glass.
[0142] (5) It can be seen from Example 4 that the single-crystal phase curved microcrystalline glass-ceramics prepared by adjusting the process parameters of the chemical strengthening treatment in the present invention has a large drop height and excellent mechanical properties.
[0143] In summary, the present invention reasonably regulates the composition of the glass composition and the content of each component, so that the prepared glass-ceramics only includes one crystalline phase, which is beneficial to improving the uniformity and light transmittance of the glass-ceramics and reducing its haze. By ensuring that the content of each component satisfies a specific quantitative relationship and then reasonably controlling the relevant parameters of the pre-crystallized glass-ceramics, the single-crystalline phase curved glass-ceramics prepared after 3D hot bending treatment has a stable crystal phase structure and uniform grain size, which is beneficial to improving the mechanical properties of the glass-ceramics. The present invention prepares a single-crystalline phase curved glass-ceramics with high light transmittance, low b value, small haze, low warping and high dimensional accuracy.
[0144] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A glass composition, characterized in that: The glass composition comprises, in terms of oxides, 2wt%-5wt% Al2O3, 2wt%-4wt% P2O5, 12wt%-15wt% Li2O, 2wt%-5wt% Na2O, 7wt%-10wt% ZrO2 and 0.1wt%-1.5wt% CaO, with the remainder being SiO2; The composition of the glass composition satisfies the following relationship, wherein ω represents the mass percentage: 0.3≤(ω(ZrO2)-ω(P2O5)) / (ω(Li2O)-ω(Na2O))≤0.75; 1.04≤(ω(ZrO2)-ω(Na2O)) / (ω(Al2O3)-ω(CaO))≤9.
2. The glass composition according to claim 1, characterized in that Calculated as oxides, the glass composition further comprises: Any one of 0-1wt% K2O, 0-1wt% B2O3, 0-1wt% ZnO, 0-1wt% MgO or 0-1wt% Y2O3, or a combination of at least two thereof.
3. A pre-crystallized glass-ceramic comprising the glass composition according to claim 1 or 2, characterized in that: The crystalline phases of the pre-crystallized glass-ceramics include Li2Si2O5 and Li2SiO3.
4. The pre-crystallized glass-ceramics according to claim 3, characterized in that: The ratio C of the crystal phase to the glass phase in the pre-crystallized glass-ceramics is 0.56-0.92; And / or, the crystal grain size D50 of the pre-crystallized glass-ceramics is ≤20nm; And / or, the thickness of the pre-crystallized glass-ceramics is 0.3 mm-0.8 mm; And / or, the average transmittance of the pre-crystallized glass-ceramics in the wavelength range of 380nm-780nm is ≥90.1%; And / or, the b value of the pre-crystallized glass-ceramics is ≤0.4, and the b value is the absolute value of the yellow-blue value when the glass thickness is 0.6 mm; And / or, the haze of the pre-crystallized glass-ceramics is ≤0.2%.
5. A single-crystal phase curved surface glass-ceramics prepared from the pre-crystallized glass-ceramics according to claim 3 or 4, characterized in that: The single crystal phase of the single crystal phase curved surface glass-ceramics is Li2Si2O5 crystal phase.
6. The single-crystal phase curved surface glass-ceramics according to claim 5, characterized in that: The crystal grain size D50 of the single-crystal phase curved surface glass-ceramics is ≤30nm; And / or, the crystallinity of the single-crystal phase curved glass-ceramics is ≤70%; And / or, the average transmittance of the single-crystal phase curved glass-ceramics at a wavelength of 380nm-780nm is ≥91%; And / or, the warping of the single-crystal phase curved glass-ceramics is ≤0.1 mm; And / or, the b value of the single-crystal phase curved surface glass-ceramics is ≤0.3, and the b value is the absolute value of the yellow-blue value when the glass thickness is 0.6 mm; And / or, the haze of the single-crystal phase curved glass-ceramics is ≤0.1%; And / or, the falling height of the single-crystal phase curved glass-ceramics is ≥1.5m.
7. A method for preparing the single-crystal phase curved surface glass-ceramics as claimed in claim 5 or 6, characterized in that: The preparation method comprises the following steps: (1) After mixing raw materials according to the composition of the glass composition of claim 1 or 2, melting, clarifying, homogenizing and annealing are carried out in sequence to obtain plain glass; (2) performing a pre-crystallization treatment on a plain plate glass to obtain the pre-crystallized microcrystalline glass according to claim 3 or 4; (3) The pre-crystallized glass-ceramics is subjected to 3D heat bending treatment to obtain the single crystal phase curved glass-ceramics.
8. The preparation method according to claim 7, characterized in that: The pre-crystallization treatment in step (2) includes a nucleation treatment; the holding temperature of the nucleation treatment is 540° C.-640° C., and the holding time is 2 h-4 h.
9. The preparation method according to claim 7, characterized in that: The 3D hot bending treatment in step (3) includes preheating treatment, hot pressing treatment and cooling treatment performed in sequence. The working temperature of the preheating treatment is 460°C-760°C, and the working time is 100s-500s; the working temperature of the hot pressing treatment is 720°C-800°C, the pressure is 0.1MPa-3MPa, and the working time is 50s-300s; the working temperature of the cooling treatment is 350°C-600°C, and the working time is 100s-500s.
10. The preparation method according to claim 7, characterized in that: After the 3D hot bending treatment, a chemical strengthening treatment is also performed; the chemical strengthening treatment includes using bath salt to perform ion exchange on the single crystal phase curved microcrystalline glass; the bath salt includes a mixed molten salt, the mixed molten salt includes NaNO3 and KNO3, and / or the mixed molten salt also includes LiNO3; the terminal temperature of the chemical strengthening treatment is 460℃-500℃, and the insulation time is 3h-6h.
11. An application of the single-crystal phase curved surface glass-ceramics as claimed in claim 5 or 6, characterized in that: The single-crystal phase curved glass-ceramics is applied to touch display screens, smart terminals or photovoltaic power generation devices.